The Effect of Problem-Based Learning Assisted by Magic Straw Media on Elementary School Students' Mathematical Conceptual Understanding - Afifah, R. Ulya; Caturiasari, Jennyta; Nurussama, Alfiana (Jurnal keilmuan dan Kependidikan dasar, 2026)
Mathematical conceptual understanding is a fundamental ability that students need to master, as it serves as the foundation for learning more complex mathematical concepts. However, elementary school students' conceptual mathematical understanding remains relatively low. This research aimed to determine the effect of the Problem Based Learning (PBL) model assisted by Magic Straw media on students' mathematical conceptual understanding. The study employed a quantitative approach using an experimental method with a one-group pretest-posttest design. The sample consisted of 20 fifth-grade students from SDIT Ilmu Purwakarta selected through purposive sampling. The research instrument was an essay test consisting of five items designed to measure students' mathematical conceptual understanding. The data were analyzed using descriptive statistics, normality tests, paired sample t-tests, and N-Gain analysis with the assistance of IBM SPSS Statistics 26. The results revealed a significant effect of the Problem Based Learning model assisted by Magic Straw media on students' mathematical conceptual understanding, indicated by a significant value of less than 0.05. Furthermore, the N-Gain score of 0.5321 indicated a moderate improvement in students' mathematical conceptual understanding. Therefore, the Problem Based Learning model assisted by Magic Straw media can be considered an effective alternative learning approach to improve elementary school students' mathematical conceptual understanding.